2014
DOI: 10.1007/s12028-014-9972-0
|View full text |Cite
|
Sign up to set email alerts
|

Reversal of Coagulopathy Using Prothrombin Complex Concentrates is Associated with Improved Outcome Compared to Fresh Frozen Plasma in Warfarin-Associated Intracranial Hemorrhage

Abstract: PCC adequately corrected INR without any increase in adverse events compared to FFP and was associated with less major hemorrhage and improved 3-month outcomes in patients with warfarin-associated intracranial hemorrhage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 71 publications
(32 citation statements)
references
References 47 publications
0
32
0
Order By: Relevance
“…A recent prospective study on 64 patients with warfarin-associated intracerebral hemorrhage demonstrated that the use of PCC for anticoagulant reversal resulted in reduced mortality and improved outcome at 3 months compared with the use of FFP. 17 Several different types of PCC are available. Although all concentrates are derived from human plasma, the main difference is their concentration of different clotting factors.…”
Section: Discussionmentioning
confidence: 99%
“…A recent prospective study on 64 patients with warfarin-associated intracerebral hemorrhage demonstrated that the use of PCC for anticoagulant reversal resulted in reduced mortality and improved outcome at 3 months compared with the use of FFP. 17 Several different types of PCC are available. Although all concentrates are derived from human plasma, the main difference is their concentration of different clotting factors.…”
Section: Discussionmentioning
confidence: 99%
“…Since WAICH expansion occurs rapidly, abrupt reversal with vitamin K in addition to fresh frozen plasma (FFP) or prothrombin complex concentrate (PCC) may be crucial in stopping progression and improving outcomes [38,39]. Not only PCC provides rapid administration and INR correction compared to FFP, in one study its use was associated with improved 3-month outcome in patients with WAICH [40]. In patients with factor Xa inhibitor-associated ICH, the available data are not sufficient to support the efficacy of available reversal agents.…”
Section: Coagulopathymentioning
confidence: 99%
“…PCCs enable a rapid correction of hemostasis without the need for excessive volume supply, and their use has been implemented in European guidelines for the reversal of anticoagulation in cases of life-threatening bleeding complications (3). Several studies have demonstrated high efficacy and a good safety profile of four-factor PCC for anticoagulation reversal in patients with ICH (4).…”
Section: Introductionmentioning
confidence: 99%